Mechanical Characterization of NaOH-Treated Agel Fiber-Cotton Composites - Santhiarsa, IGN Nitya; Kusuma, I Gusti Bagus Wijaya; Negara, I Gede Artha (Journal of Mechanical Engineering Science and Technology (JMEST), 2023)
Composites comprising two or more distinct materials are fabricated to enhance the mechanical properties of the constituent materials. A common approach for generating composites is vacuum infusion. This technique enables the infusion of two materials utilizing a vacuum. In the field of composite science, textile composites have emerged as an important new development. Agel rope, derived from twisting agel fibers, exhibits inferior bending strength and elongation compared to ropes fabricated from synthetic fibers. Moreover, agel rope is susceptible to bacterial decay. This study aims to characterize the mechanical properties of textile composites comprising woven agel rope subjected to NaOH treatment. Specimens in the longitudinal (warp) shows maximal load bearing capacity, as determined by experimental results. Samples treated with 5% NaOH tolerated peak loads of 51.12 N prior to failure, with an associated deflection of 3.18%. Specimens in the transverse (weft) of the woven cotton demonstrated maximum load of 40.75 N at 0.9% deflection. The maximum stress was 25.67 MPa. Similar to agel rope, NaOH treatment removes adhering contaminants from cotton fibers, thereby enhancing their strength. However, NaOH concentrations exceeding 7.5% extract cellulose, damaging the fiber ultrastructure.